COMPLEMENTARY INSTITUTIONS FOR FUNDING REGIONAL ECONOMIES - G. B. Korovin; E. A. Krokhina (Финансы: теория и практика, 2017)
With long-term funding resources unavailable, the real sector of the domestic economy is deprived of the opportunity to boost the investment activity. The structure of the investment sources shows the predominant role of the banking system and budgetary funding in this process. The large-scale goals of the domestic economy, along with the needs of the new industrialization, require not only implementation of large investment projects but also the use of new approaches to the monetary policy as well as the improvement of basic and complementary institutions for funding the real sector of the economy. It is the development of complementary institutions that can substantially increase the investing effectiveness. With this purpose the paper examines regional banking structures and non-bank funding institutions. The research methods included the institutional analysis, the structural and dynamic analysis of the Bank of Russia data and regional statistics. It is determined that the Russian economy needs more regional institutions, particularly regional banking networks and government structures, to support the real sector. Their advantages are the ability to take into account the specifics of regional businesses, knowledge of customers, flexibility, efficiency in decision-making, individual approach, the ability to establish partnership relations and neutralize possible shortcomings of federal institutions. At the same time, it is confirmed that the regional banking network in Russia tends to shrink due to tightening of laws introduced and violation of competition rules by large banks. The effects of low activity in the sphere of lending to small and medium-sized businesses related to restrictions in capitalization of regional banks, slow capital accumulation rates as well as the limited access to the interbank lending market and the CBR refinancing system have been revealed. The paper determines the complementary nature and role of the emerging system of state institutions for funding the real sector of the economy. It is noted that today these institutions do not possess significant resources, are poorly coordinated and lack a strict system of performance indices. The role of the regional business support infrastructure being established in a number of industrial regions is assessed based on the data of the Sverdlovsk Region as a traditional industrial region of the Russian Federation.